A sustainable lean production framework based on inverse DEA for mitigating gas flaring. (15th November 2022) - Orisaremi, Kelvin K.; Chan, Felix T.S.; Chung, S.H.; Fu, Xiaowen
Highlights: Inverse DEA models are proposed for implementing lean practices. Lean potential growth has been incorporated in proposed models. Inverse DEA has been applied to turbine power generation. The interrelationship between oil production and gas flaring has been examined. Abstract: The gas flaring process remains a significant contributor to climate change due to the release of greenhouse gases. Additionally, it denies oil-producing nations access to affordable energy sources. With climate change gaining momentum and in accordance with the global gas flaring reduction partnership (GGFR), oil and gas production managers must adopt an approach that can be both environmentally and economically beneficial. As such, this study proposes a novel application of the inverse data envelopment analysis (DEA) model for implementing lean production practices in the petroleum industry. Using inverse DEA methodology, a three-stage inverse problem involving selected oil-producing nations during the 2015 production year was solved. Stage one found that by incorporating lean practices, all the efficient producers were able to increase oil production by 50, 000 barrels without increasing their current levels of flared gas. For the second stage, a reduction in gas flaring was imposed on the efficient producers to achieve the same production targets as stage one. Gas flaring reductions for Angola, Iraq, Libya, and Nigeria were computed to be 13.75%, 4.59%, 25.24%, and 54.93 %, respectively. A simple cycle gas turbine, such as the GT13E2, was used for all four nations to convert these reductions into gross power outputs of 300 MW, 150 MW, 450 MW, and 2250 MW, respectively, with Nigeria clearly benefiting the most. In the third stage, the concept of lean potential growth was integrated into an improved model to rank efficient oil producers. Saudi Arabia was found to be the most efficient producer, partly explaining why no reductions in gas flaring were obtainable for the nation in stage two. Based on our findings, we recommend the proposed models and new concepts for improving operational sustainability in the petroleum industry.